Managing multipartner strategic alliances - Das, T. K. 1938- (Research in strategic alliances., 2015)
Managing Multipartner Strategic Alliances is a volume in the book series Research in Strategic Alliances that focuses on providing a robust and comprehensive forum for new scholarship in the field of strategic alliances. In particular, the books in the series cover new views of interdisciplinary theoretical frameworks and models, significant practical problems of alliance organization and management, and emerging areas of inquiry. The series also includes comprehensive empirical studies of selected segments of business, economic, industrial, government, and non-profit activities with wide prevalence of strategic alliances. Through the ongoing release of focused topical titles, this book series seeks to disseminate theoretical insights and practical management information that should enable interested professionals to gain a rigorous and comprehensive understanding of the field of strategic alliances.Managing Multipartner Strategic Alliances contains contributions by leading scholars in the field of strategic alliance research. The 10 chapters in this volume cover a number of significant topics related to the formation, operation, and performance of multipartner strategic alliances (i.e., alliances with more than two members) that are increasingly being formed in various industrial sectors. The chapter topics cover both the broader issues, such as the peculiar complexities of multipartner alliances that arise because of indirect or generalized reciprocities among its multiple members vis--̉vis the direct reciprocity within dyadic or two-member alliances, and the roles of power and multilevel embeddedness, and the more focused topics of managing triadic alliances, the evolution of an airline alliance, and the nature of value creation in a consortium. The chapters include empirical as well as conceptual treatments of the selected topics, and collectively present a wide-ranging review of the noteworthy research perspectives on the nature, management, and performance of multipartner alliances.